"To Grasp the Gaping Grave:" Blackness, Death, and the Afterlife of Slavery in Unathi Slasha's Jah Hills. Issue 2 (2nd July 2020) - Milazzo, Marzia
Abstract : This essay reads Unathi Slasha's Jah Hills (2019 [2017]) in light of Afropessimism to argue that the novel articulates a grammar of Black suffering and offers a staunch critique of antiblackness and white supremacy. Through the character of Jah Hills, who inhabits the limbo between life and death, the novel reflects upon how slavery continues to shape the ontological position and everyday lives of Black people as they remain subjected to premature death. In the process, Jah Hills throws white theories of precarity into crisis as well as disrupts the antiblack politics of sentimentality as the story is told from the perspective of Jah-turned-isithunzela, a creature that, rather than primarily eliciting the sympathy of the reader, wreaks havoc on the living. An extended meditation on the political ontology of Blackness, Jah Hills can be read as an allegory of the Black condition, one that is not simply defined by precarity, but by a more fundamental deprivation as life itself is not guaranteed.